Factors Affecting Medical Faculty Students' Choice of Specialization and Trends in Branch Preferences - Semih Musa Coskun; Osman Sezer Cinaroglu; Umut Onbasioglu; Sevval Celik; Irmak Yakut; Gorkem Can Duran; Nesrin Aslan (Izmir Katip Celebi University Faculty of Medicine, 2026)
Objective: This study evaluated the factors influencing medical students’ specialty preferences, career plans, and trends in specialization selection. Materials and Methods: This prospective, descriptive survey study was conducted among students at Izmir Katip Celebi University Faculty of Medicine. Data were collected from November 15, 2025, to March 15, 2026, using a structured online questionnaire. Although the initial dataset comprised 188 responses, the final analysis included 162 students after excluding records with missing or incomplete data. The variables evaluated included sociodemographic characteristics, intention to pursue specialty training, perceived specialty groups, the influence of the Turkish Medical Specialty Examination (TUS), priorities in specialty selection, considerations of postgraduate training abroad, and factors influencing career choices. Categorical variables were expressed as frequencies and percentages, whereas age was presented as median and interquartile range (IQR). Chi-square tests were utilized for group comparisons. Results: The median age of the participants was 21 years (IQR = 20–22), and 89 students (54.9%) were female. Overall, 144 participants (88.9%) intended to pursue specialty training, while 77 (47.5%) considered obtaining specialty training or education abroad. The most frequently selected specialty groups (respondents could select more than one) were surgical specialties (61.1%), followed by internal medicine specialties (39.5%) and basic medical sciences (16.7%). The leading factors influencing specialty choice were alignment with personal interest and ability (78.4%), lifestyle compatibility (73.5%), income level (66.7%), working hours and on-call workload (64.2%), and the stress level associated with the specialty (62.3%). No statistically significant differences in specialty preferences were found based on gender or academic phase. Conclusion: Medical students showed a strong tendency toward specialization. Specialty choice was shaped not only by personal interest and ability but also by lifestyle expectations, income, working conditions, and stress level.